Reproductive Factors and Breast Cancer Risk in Lithuanian Women: A Population-Based Cohort Study - Steponavičienė, Laura; Vansevičiūtė, Rasa; Zabulienė, Lina; Jasilionis, Domantas; Urbonas, Vincas; Smailytė, Giedrė (Acta medica Lituanica, 2020)
Background. Although the relationship between reproductive factors and breast cancer is internationally proved, reliable data on former USSR countries are scarce. This study examines the association of parity, age at the first childbirth, number of children, and breast cancer risk in Lithuanian women. Methods. The study that included women from 40 to 79 years old was based on a dataset that was made up linking all records from the 2001 census, all cancer incidence records from the Lithuanian Cancer Registry and all death records from Statistics Lithuania between 6th April 2001 and 31st December 2009. Cox’s proportional hazards regression models were used to estimate the hazard ratios (HRs) for parity, age at the first childbirth, and number of children. Results. If compared to nulliparous women, parous women had a lower risk of breast cancer (HR=0.84, 95% CI 0.78–0.89) and this risk further decreased with an increasing number of children. Women who gave birth after the age of 25 had a significantly higher risk of breast cancer. This disadvantage became statistically insignificant or decreased after controlling for total number of children. Conclusions. Parity and age at the first childbirth are strong predictors of breast cancer risk among Lithuanian women.